Aggregation Regulated Ultrafast Singlet Fission Pathways in TIPS-Pentacene Films - Guang Huang; Junzi Li; Zilin Zhou; Zongtao Huang; Wei Kong; Fangteng Zhang; Youjun Zeng; Guanyu Liu; Tingchao He; Lin Ma (Ultrafast Science, 2024)
Singlet fission (SF) is a spin-conserving process converting 1 singlet exciton into 2 triplet excitons. This exciton multiplication mechanism offers an attractive route to solar cells that circumvent the single-junction Shockley–Queisser limit. However, it remains unclear how intermolecular coupling, which is subject to the aggregation extent in thin-film morphology, controls SF pathways and dynamics. The prototype molecule 6,13-bis(triisopropylsilylethynyl)-pentacene (TIPS-pentacene) has been extensively studied to investigate SF mechanisms. However, previous literature reports have presented divergent SF mechanisms and pathways in TIPS-pentacene films. In this study, solvent vapor annealing treatment is used to deliberately adjust the aggregation extent in TIPS-pentacene films. This enables us to reproduce various SF pathways reported in the literature under the same experimental conditions, with the only variation being the level of aggregation. These results shed light on the crucial role that molecular aggregation plays in modulating both the SF mechanism and pathway and reconciles the previously contentious SF mechanisms and pathways reported in TIPS-pentacene films. Our study offers substantial insights into the understanding of the SF mechanism and provides a potential avenue for future control of SF pathways in accordance with specific application requirements.